Book Review: Alexander de Frailas Barbosa, Maria Cristina Cacciamali and Gerry Rodgers, Growth and Inequality: The Contrasting Trajectories of India and Brazil. Issue 2 (August 2018) - Reddy, D. Narasimha
Alexander de Frailas Barbosa, Maria Cristina Cacciamali and Gerry Rodgers, Growth and Inequality: The Contrasting Trajectories of India and Brazil . New Delhi: Institute for Human Development and Cambridge, Cambridge University Press, 2017, xxvi + 349 pp.